Tinjauan Penanganan Limbah Medis Padat di Puskesmas Gunung Putri Kabupaten Bogor Tahun 2023: Review Of Solid Medical Waste Handling At Puskesmas Gunung Putri Bogor District Year 2023 - Siti Nurrinda Sari; Kahar Kahar (Jurnal Diskursus Ilmiah Kesehatan, 2023)
Background: Gunung Putri Health Center is one of the produce of medical waste. The process of handling solid medical waste has problems at the stages of transportation and temporary storage. Aims: The purpose of this study is to determine the handling of solid medical waste, the infrastructure for handling solid medical waste, the science and action of healthy and cleaning workers. Methods: The research method used descriptive. Sampling technique using purposive sampling, the sample for this study is 27 people, there is 6 rooms observed produce solid medical waste. Results: The results showed that the generation of solid medical waste is 0.87 kg/day. Treatment of solid medical waste at the sorting stage 100% qualified, 67% of the requirements for the container stage, the in-situ transportation stage not qualified, the ex-situ transportation stage 100% qualified , the temporary storage stage not qualified, waste handling infrastructure facilities 100% qualified for solid medical sorting and storage stage, in-situ transportation stage and temporary storage stage are not eligible. Aspects of the knowledge of health and cleaning workers 25 respondents (92.6%) in the "good" category, 2 respondents (7.4%) in the "enough" category. The behavior aspect of the health of workers from 26 respondents was 100% in the "good" category, and the behavior of cleaners from 1 respondent was in the "less" category. Conclusion: The conclusion is that the handling of solid medical waste and infrastructure does not meet the requirements, the science and action of healthy workers is in a good category. The knowledge of the cleaning staff is in the sufficient category and the behavior is lacking. It is expected that in-situ transportation will be carried out every day or less than 1 day if the waste is filled with 3/4 of the volume of the container, increasing the availability of TPS at the Gunung Putri Health Center.